Relationship between Family History of Hypertention and Autonomic Nervous System Activity - Ambasari, Rika Putri; Sarosa, Hadi; Muhtarom, Muhtarom (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2013)
The most common hypertension is essential hypertention influenced by genetic factors. Autonomicic nervous activity is influenced by several factors including genetic. This study aimed to determine the relationship between family history of hypertension and autonomic nervous system activity. In this observational analytic cross sectional study, out of 124 a students of the Medical Faculty, University Islam Sultan Agung Semarang 44 students were included using simple stratified method consisting of 22 men and 22 women aged over 20 years. The subjects were asked for family history of hypertension, orthostatic and valsalva examination. 25 students (56.8%) had a family history of hypertension and experienced imbalance of autonomic nervous activity. Out of 19 students (43.2%) without a history of hypertension, 10 people (22.7%) had a balance of autonomic nervous system activity and 9 people (20.5%) experienced imbalance of autonomic nervous system activity. Fisher correlation test results showed a significant association (p < 0.05) and correlation test of Lamda resulted in p value of 0.100, indicating a very week positive correlation. The study concludes that there was a correlation between a family history of hypertension and on autonomic nervous system activity with a very weak relationship.